The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1097/fpc.0b013e32835a0ffa
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation-optimized treatment benefit of angiotensin-converting enzyme inhibitors in patients with stable coronary artery disease

Abstract: ACE inhibitors were associated with a significant decrease in MACE in Chinese patients diagnosed with CAD. Genetic variants were also associated with event-free survival, but their effects were modified by the use of ACE inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Lee et al also reported that ACEI was associated with lower risk for ISR and subsequently lower need for revascularization. Moreover, it indicated that DD genotype of ACE gene was correlated with higher incidence for revascularization [21].…”
Section: Discussionmentioning
confidence: 98%
“…Lee et al also reported that ACEI was associated with lower risk for ISR and subsequently lower need for revascularization. Moreover, it indicated that DD genotype of ACE gene was correlated with higher incidence for revascularization [21].…”
Section: Discussionmentioning
confidence: 98%
“…The I allele, which represents an insertion of 287-base pair (bp), is associated with lower serum and tissue, and the deleted form of the variant (D allele) is associated with higher circulating and tissue ACE activity [ 19 , 20 ]. This genetic polymorphism was associated with coronary artery disease [ 21 ], systemic lupus erythematosus [ 22 ] and cancer risk [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the wide range of candidate genes, structural polymorphism of which may have a prognostic value in development and progression of congestive heart failure, special attention in current studies is directed to genes of components of rennin-angiotensin-aldosteron system and counterregulatory systems, including β-adrenoreceptors genes [3].…”
mentioning
confidence: 99%